Subtitle Translation Strategy: Cross-Cultural Translation of Japanese Kuso's Profanity Words - Murniati Br Barus (TALENTA Publisher, 2024)
The translation of subtitles in an animation is crucial for understanding the message sent to the viewer. The objective of this research is to determine effective methods for translating Japanese kuso profanities into Indonesian. The utilized data is sourced from Hakyu anime, which prominently features a substantial amount of obscenity, particularly the term